ANALISIS MODEL EMPOWERING LEADERSHIP DALAM OPTIMALISASI DI ERA NEW NORMAL PADA ENVY RESTAURANT - I Made Mai Noval; A.A. Istri Agung Maheswari; Ni Komang Ayu Budiastriani; A.A.Ngr. Oka Suryadinatha Gorda (Jurnal Pendidikan Ekonomi (JURKAMI), 2022)
The business sector at this time has severe challenges, due to the lack of income earned which gives a threat to the sustainability of a business. At this time the company leader is expected to be able to apply the right leadership and is expected to be able to encourage employees to contribute more. The purpose of this study is to examine the Empowering Leadership model in optimization in the New normal Era in one of the business fields engaged in the sale of food and beverage products, namely Envy Restaurant. This study uses qualitative and quantitative types of data, using data collection techniques through interviews, observations, and documentation. The informants in this study were 6 people chosen using purposive sampling techniques. The results of this study found that leaders at Envy Restaurant implemented empowerment to employees in the form of support that was seen from certain aspects such as employee motivation, trust and self-efficacy